Dietary changes in early-stage breast cancer patients from pre-surgery and over the 12 months post-surgery. Issue 2 (28th January 2021) - Brunvoll, Sonja H.; Thune, Inger; Bertheussen, Gro F.; Fjeldheim, Frøydis; Flote, Vidar G.; Frydenberg, Hanne; Lundgren, Steinar; Skjerven, Helle; Lømo, Jon; Fagerland, Morten W.; McTiernan, Anne; Schlichting, Ellen; et al.
Abstract: The time after a breast cancer diagnosis is a potential period for making positive dietary changes, but previous results are conflicting. The main aim of the present study was to study breast cancer patients' dietary changes during the 12 months post-surgery and from 12 months pre-surgery to 12 months post-surgery with repeated administration of a 7-d pre-coded food diary and an FFQ, respectively. Women ( n 506), mean age 55·3 years diagnosed with invasive breast cancer (stages I and II), were included. The dietary intake was quite stable over time, but the intake was lower for energy (0·3 and 0·4 MJ/d), alcohol (1·9 and 1·5 g/d) and vegetables (17 and 22 g/d) at 6 months than 3 weeks post-surgery (food diary) and at 12 months post-surgery than pre-surgery (FFQ), respectively. Furthermore, energy percentage (E%) from carbohydrates increased between 0·8 and 1·2 E% and E% from fat decreased between 0·6 and 0·8 E% over time, measured by both dietary assessment methods. We observed a higher intake of dairy products (11 g/d) at 6 months post-surgery (food diary), and a lower intake of dairy products (34 g/d) and red and processed meat (7·2 g/d) at 12 months post-surgery (FFQ). Moreover, 24 % of the patients claimed they made dietary changes, but mostly they did not change their diet differently compared with those patients who claimed no changes. In conclusion, breast cancer patients reported only minor dietary changes from 12 months pre-surgery and during the 12 months post-surgery.